Succession of a bacterial rhizospheric community along a chronosequence of a cold desert - F. Mapelli; B. Scaglia; R. Marasco; A. Balloi; E. Rolli; F. Tambone; F. Adani; S. Borin; D. Daffonchio; G. Tsiamis; S. Vasileiadis; K. Bourtzis (2012)
Global warming and ongoing climate changes result in glacier retreat at different latitude and altitude on Earth. Ice melting determines the exposure of a barren mineral substrate subjected to the processes of primary colonization and soil formation. Chronosequences can be identified on glacier moraines, where the increasing distance from the forefront corresponds to the increase of time of permanence out of ice and to ecosystem development. Shifts of microbial and plant communities over time are defined as succession, which can be influenced by several factors over a forefield chronosequence. To describe the ecological succession of the microbiome composition during primary succession of high arctic soils we identified an endemic vascular plant present in the whole transect of the Midtre-Loveénbreen glacier, namely Saxifraga oppositifolia, and we analyzed the associated rhizospheric communities and the corresponding bulk soils. In the present study we applied cultivation-independent methods to investigate (i) the role of successional stages and (ii) the influence of the host plant on the microbial community inhabiting both bulk and rhizospheric soils collected from seven stations of a chronosequence on the forefront of the Midtre-Loveénbreen glacier (78°53’N, Svalbard Islands, Norway), distinguished by increasing levels of soil fertility and plant colonization (Hodkinson et al., 2003). Detailed description of the rhizospheric microbiome realized by Denaturing Gradient Gel Electrophoresis, 16S rRNA clone libraries and PhyloChip analyses revealed a complex bacterial community in all the successional stages. Bulk and rhizospheric soils hosted different microbial communities, although the rhizosphere microbiome in the youngest soils was more similar to those of bulk soils than to the older rhizospheres. The results indicated therefore that the structure of the bacterial communities colonizing the S. oppositifolia rhizosphere is shaped by the presence of the plant together with the degree of soil development. The ...